Pengaruh Rasio Likuiditas Terhadap Kinerja Keuangan Triwulan Bank Muamalat Indonesia Periode 2015-2022 - Rohmah, Zaitur; Syarifah, Wardatus (FEB Universitas Sultan Ageng Tirtayasa, 2023)
Financial performance can show the quality of the bank through the calculation of financial ratios, one of which is the liquidity ratio. Bank Muamalat Indonesia's cash has decreased for 2 years after Covid-19 and at that time Bank Muamalat's ROA also stagnated. This research uses quantitative methods using secondary data obtained from Bank Muamalat Indonesia's quarterly report 2015-2022. Data analysis using multiple linear regression. This study was conducted to determine the effect of liquidity ratios on financial performance partially and simultaneously. From the results of this study, that partially the variable liquidity ratio Current Ratio (CR) does not have an influence and is significant on financial performance (ROA). Cash Ratio (CSH) does not have a positive influence on financial performance (ROA). Working capital to assets ratio (WCTA) has a positive and significant influence on financial performance (ROA). Current Ratio (CR), Cash Ratio (CSH) and Working Capital to Total Assets Ratio (WCTA) simultaneously affect Bank Muamalat Indonesia's financial performance.